The effect of superovulation prior to mating on fetal growth in Iambs from Javanese thin-tail ewes - Manalu, W (Indonesian Animal Sciences Society, 1999)
Twenty-nine fetuses (11 fetuses from 9 non-superovulated ewes and 18 fetuses from 8 superovulated ewes) were used to study the effect of superovulation of ewes prior to mating on fetal weight, fetal length, the length of the body and limbs, chest circumference, weights of the body, head, neck, limb, and viscera. Superovulated ewes, though with a higher litter size, had a greater fetal growth as was indicated by the greater fetal weight and length, the length and weight of the body and limb on day 49 of pregnancy. On day 105 of pregnancy, superovulated ewes with multiple fetuses (â¥3) had similar fetal growth than nonsuperovulated ewes with single and twin fetuses. However, superovulated ewes with a single fetus had greater fetal growth as was shown by the greater fetal weight and length, the length of the body and limbs, chest circumference, and weight of the body, limb, and viscera when compared to those non-superovulated ewes with a single or twin fetuses. The results of the experiment suggested that superovulation of ewes prior to mating could be used to improve fetal prenatal growth during pregnancy Â Key words: Superovulation, fetal growth, pregnancy, sheep